Virulence Properties of the Legionella Pneumophila Cell Envelope - Shevchuk, Olga; Jäger, Jens; Steinert, Michael (Frontiers in Microbiology, 2011)
The bacterial envelope plays a crucial role in the pathogenesis of infectious diseases. In this review, we summarize the current knowledge of the structure and molecular composition of the Legionella pneumophila cell envelope. We describe LPS biosynthesis and the biological activities of membrane and periplasmic proteins and discuss their decisive functions during the pathogen-host interaction. In addition to adherence, invasion and intracellular survival of L. pneumophila, special emphasis is laid on iron acquisition, detoxification, key elicitors of the immune response and the diverse functions of outer membrane vesicles. The critical analysis of the literature reveals that the dynamics and phenotypic plasticity of the Legionella cell surface during the different metabolic stages requires more attention in the future.